African Identities, Afro-Omani Music, and the Official Constructions of a Musical Past - Harthy, Majid H. al- (The World of Music, 2012)
Based on dissertation research in the port city of Sur, historically significant both for trans-oceanic seafaring and trade, and more specifically for its connection to the east coast of Africa, this article analyzes the African-derived performance genres that dominate Sur's music scene within an ever-elusive concept of Africa. The sacred healing rituals zār, mikwarā, and ṭambūra; and the secular genres, mdema, and fann is-ṣawt have been renamed funūn taqlīdīya or traditional arts, national nomenclature that collects the myriad traditions of the country while marginalizing differential identities. Rhetorically, Suri musicians not only adopt, they also emphasize their national Omani identity, while expressing their African identity as of the "other." Musically, however, their approach to performance, including the use of Swahili texts, the predominance of body movement, and multi-layered musical textures produced by a variety of instruments from East Africa, reveals, I argue, the musicians' African identity as a "self." The seemingly binary "self" identities articulated by Suri musicians through two differing modes of expression (rhetoric and performance) illustrate not only the problematic nature of the concept of Africa in Oman, but also highlights how simplistically the African presence in Oman has been treated in the music scholarship of this country.
Keywords: Musique – Oman

The Musical Design of National Space and Time in Oman - Rasmussen, Anne K. (The World of Music, 2012)
This article unpacks ethnographic research conducted in 2010–2011 and in 2012 among cultural activists and reformers who are using music as a generative force toward the development of collective identities in a geopolitical space. I analyze three domains of cultural production and consider how the Sultan's initiatives have resulted in the embodiment of artistic consumption and connoisseurship that are required for musical life in the public sphere: first are the Sultan's privately controlled military bands, Arab music ensembles, and symphony orchestra; second are public arts festivals that nurture and celebrate traditional music and dance; third is the domain of Omani popular music facilitated by Arab regional interculturalism and media flows that depend significantly on practitioners from Egypt, Iraq, and other Gulf states. I show how these domains of music and dance work to enable the imagination of a cultural space and time for Oman and its historical and contemporary relationships with the Arab world, Africa, Asia, and "the West." The ethnographic focus on the Salalah Festival in the Dhofar province, provides a close-up shot of the workings of the state at the local level in a context that is both far from the control of the capitol city, Muscat, but that also reproduces many of the relations of dominance and resistance that is an inevitable artifact of political power and cultural policy.
Keywords: Musique – Oman

On the Decks of Dhows: Musical Traditions of Oman and the Indian Ocean World - Ulaby, Laith (The World of Music, 2012)
This article situates the musical traditions of Oman in the broader context of the Arabian Peninsula and Indian Ocean. Trade, slavery, and pilgrimage prompted the creation of networks that extended across the Indian Ocean for hundreds of years and facilitated deep and lasting cultural exchanges. Oman has played an important role in these networks and this is deeply reflected in many of the local musical traditions. Since about the middle of the 20th century, countries in the Arabian Gulf (sometimes referred to as the GCC, Gulf Cooperation Council, plus Yemen) have made strides toward establishing independent nationalism in the contemporary race for unique identities; however, their histories, peoples, and musical traditions, particularly those of nomadic Bedouins and coastal seafaring populations, have overlapped for many centuries. I attempt to sketch out some comparisons, particularly in terms of performance practice, between Oman and the rest of the Gulf States with a focus on maritime music, the music that occurred "on the decks of dhows," the traditional sailing vessel of the Arabian Gulf. My theoretical grounding for this article engages with frameworks for cultural transmission and explores their relevance to the Gulf. By looking at historical accounts and previous scholarship, alongside ethnographic research, I describe some of the conduits for sharing musical influence with the broader Indian Ocean cultural space. Lastly, I critically examine some of the historiographies that have been created around these exchanges and their valence to the political economy of cultural heritage in the region.
Keywords: Musique – Oman

Music in Oman: an Overture - Harthy, Majid H. al-; Rasmussen, Anne K. (The World of Music, 2012)
Keywords: Musique – Oman